Stomach Content Analysis of Tilapia Fish (Oreochromis mossambicus) in Talaga Lake Waters Donggala Regency - Faried, Dirham; Trianto, Manap (BIO-EDU: Jurnal Pendidikan Biologi, 2020)
Tilapia fish (Oreochromis mossambicus) is a type of freshwater consumption fish, flat body shape with grey, brown or black colour. The purpose of this study was to describe the types of food found in the stomach of tilapia fish (Oreochromis mossambicus) in Talaga Lake, Donggala Regency. This research was conducted in April 2019. The method used in this study was a volumetric occurrence frequency method by a surgical sampling of fish to extract the stomach and analyze it. Based on the results of the analysis of the stomach contents of the Mujair fish (Oreochromis mossambicus), two groups of feed were obtained, namely Vegetable food (Fitoplaknton) in the form of Navicula placentula, Schroederia segitera, Schoroederia anchora, Zignemopsis circumcaniratum, Anabaena sp, Oscillatoria princeps, Spirogyra protifica, Bacillaria sp, Nitzschia aetinastroides, Oedogonium sp, Coelastrum chodati, and animal feed (Zooplankton) in the form of Tubipex sp, Brachionus havanaensis, Cyclops sp, Carcinus sp, Arcella sp, Acetes sp.